KITE GAMES SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN KOORDINASI SENSOMOTORIK PADA ANAK AUTIS - Swastika, Risma Arindha; Pawestri, Retno Dwi; Martadi, Husein (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This research is aimed at revealing the effectiveness of “Kite Games” in improving thesensomotoric coordination ability of the autistic children.The type of the research is quasi experiment by employing the quantitative approach.The pre test, treatment, and post test were implemented to improve the ability of thesensomotoric coordination of the autistic children. The research variables were the use ofKite Games as the free variable and the sensomotoric coordination ability as the boundvariable. The research subjects were autistic elementary school children meeting certaincriteria. The data were collected through observations, interviews, and tests.With the success criteria of 80%, two children met the criteria. So, the kites were effectiveto improve the sensoric coordination ability. It shows that the kites as media could bedeveloped into a more innovative media. The improvement o f the social interaction abilityof the children was shown in their willingness to initiate a communication with others.Key words: kites, autism, sensoric coordination